Determinants of Dental and Oral Hygiene in School-Aged Children - Zurriyatun Thoyibah; Haryani; Zuhratul Hajri (Jurnal Ilmiah Kesehatan, 2023)
Dental disease is an essential concern due to the vulnerability of the school-age group to dental and oral health problems. This study analyzes the correlation between knowledge and attitude toward oral and dental hygiene, tooth brushing behavior, and parental roles with dental and oral hygiene in school-aged children (10-12 years). This research method was descriptive-analytic with a cross-sectional design. The population in this study were students in grades 4, 5, and 6 at SDN 30 Mataram, totaling 120 people. There were 50 respondents with a simple random sampling. Instruments to assess knowledge, attitude, and parental roles were a questionnaire. In addition, Oral Hygiene Index-Simplified (OHI-S) to measure dental and oral hygiene, and an observation sheet to evaluate brushing teeth practice. The data analysis technique used Chi-Square to determine oral and dental health determinants in school-age children. There was a significant correlation between knowledge and attitude toward dental and oral health, tooth brushing behavior, and parental roles with dental and oral hygiene in school-aged children with significant values sequentially, p=0.006, p=0.000, p=0.000, p=0.000. In conclusion, The determinant of dental and oral hygiene in school-aged children are knowledge and attitude toward oral and dental health, teeth brushing practice, and parental roles.